KEDUDUKAN PERUSAHAAN ANJAK PIUTANG DALAM HAL PIHAK NASABAH WANPRESTASI - Hari Purnayasa Tanaya, Ketut; Rudy, Dewa Gede; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013)
The position of factoring company in customer breach of contracts. Factoring isa finance activity which buying the short term receivable of a company includingcharges of it. Transfer of receivables in a factoring agreement consist of several party,there are the client, the client of factoring company and costumers party. Receivablesthat arise from a transaction trade between the client and costumers party, because itneeds capital to the company, the client can sell their receivable to the companies’factor. The Research that have done with this writing is an normative legal study. Thisjournal will explain about the position of factoring company during on transfer ofreceivables in an agreement of factoring. On the other hand this journal also explainsabout the legal consequences that will occur if the debtor breach of contracts inagreement of factoring. The purpose of this research is to know and understand thepositions of factoring company party at transfer of receivable in agreement of factoring,and to know and understand about the consequence if debtor breach of contract inagreement of factoring. The position of factoring company party in transfer ofreceivable in transfer of receivable in factoring agreement as new creditor base onarticle 1400 of civil law book. The consequence that will occur in debtor breach ofcontract in factoring agreement, depends on type of factoring agreement that choose byevery party, if every party choose kind of resource factoring it will cause debtor breachof contract will responsible for customer party because of its inefficient, if every partychose kind of factoring agreement without recourse factoring it will makes only thefactoring company takes the responsible for the inability of debtor party.
Keywords: Factoring, Receivables, Transfer, Company